If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -7x = 5x + -8x + 18 Reorder the terms: 6 + -7x = 18 + 5x + -8x Combine like terms: 5x + -8x = -3x 6 + -7x = 18 + -3x Solving 6 + -7x = 18 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 6 + -7x + 3x = 18 + -3x + 3x Combine like terms: -7x + 3x = -4x 6 + -4x = 18 + -3x + 3x Combine like terms: -3x + 3x = 0 6 + -4x = 18 + 0 6 + -4x = 18 Add '-6' to each side of the equation. 6 + -6 + -4x = 18 + -6 Combine like terms: 6 + -6 = 0 0 + -4x = 18 + -6 -4x = 18 + -6 Combine like terms: 18 + -6 = 12 -4x = 12 Divide each side by '-4'. x = -3 Simplifying x = -3
| -2(x^2+60x-16140)=0 | | 3=-7n+12+3n | | 2r+5r-8r=9 | | 7f+7=3f+39 | | x=-3(6-8) | | 2x^2+7x+6=6 | | 36=-3(x-8) | | 4x^2+1=17 | | 5-4y-y-1=-23 | | 5x+2-2x=9+7 | | 3x+x-5=2(2x-3)+1 | | 7y=90+6 | | 150m-125m+33775=35525-150m | | 1-7m-3m-6=6 | | 5=x+3(x-5) | | 30t+15m=510 | | 6-17x=-104+32x | | solve-7x-9=-5x+7 | | -7=x+3(x-5) | | 40+0.05x=200 | | -19=x+3(x-5) | | 6x+2=27 | | x^2+12=1 | | 30t+15m=375 | | (x+1)(4x+1)=52 | | 0.15x=200 | | x+6=-x-16 | | x=-8+4(8-12) | | 30t+15m=255 | | X+3(x+4)=64 | | 20y^2+33y+10=0 | | x=-0+4(0-12) |